(untitled) (Research, Society and Development, 2024)
The present work aimed to implement an engineering solution to treat failures of the blade rotation reducing component, minimizing costs and increasing the reliability of a fleet of motor graders in a large mining company, located in the Alto Paraopeba region, in Minas Gerais. To achieve the proposed objective, the action research methodology was applied, with the close participation of the researcher. The data collection process began in January 2022. In addition to the main author’s participant observation, historical data was found from January 2018 to January 2022, relating to breakdowns and maintenance costs of swing reducers of the blade. After implementing the improvement in the preload procedure for motor grader blade rotation reducers, in 2022, it was found that there was no early breakdown of the component until the research was completed, increasing the availability and reliability of the equipment and the significantly reducing maintenance costs. As a result, it was possible to avoid the breakdown of approximately 25 speed reducers and avoid the disbursement of R 2.656.554,06, on average per year. It can be said that it achieved the objectives proposed in the article, since it was possible to completely eliminate unexpected stops due to breakage of the swing reducers with the application of the new preload procedure.